Examining Mobile-assisted Language Learning as an Autonomous Writing Tool for Indonesian Secondary EFL Students - Purwaningrum, Adriani Yulia; Lengkanawati, Nenden Sri; Yusuf, Fazri Nur (Register Journal, 2024)
The integration of technology into education has illuminated new dimensions of English Language Teaching (ELT) practices. Although technology-assisted language learning has been introduced in the EFL context for some time, its application as an autonomous learning tool for teaching writing skills remains underdeveloped. This study aims to examine the impact of Mobile-Assisted Language Learning (MALL) when employed as an autonomous learning tool on EFL students’ writing skills. Utilizing a qualitative case study design, data were collected through observations, interviews, and document analysis. The findings were categorized into two main themes; the degree of autonomy achieved and the students’ learning behaviors. The results indicate that the advantages of MALL significantly contributed to enhancement of students’ autonomous writing skills, as evidenced by an increase in the average writing score from 57.25 to 67.7. This study concludes that both the benefits and limitations of MALL implementation must be considered, as they present significant impacts and potential challenges in achieving a high-quality ELT classroom. Finally, the insights from this study may provide valuable guidance for teachers seeking to incorporate MALL into their writing classroom.